(3Jbhje GdCHOGf aj JOHjQ GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3Gfg deG cGfJ GdCOhjI hGdCZPjI eGOI dMaX UMI GdEfSGf agjhdi ddeOGhGJ ef mCbGe GdCHOGf cGf ef GdhGLH Ydi GdWHjH eYQaI eGgjJgG s
(3BNQgG (B:s
(3LOhd HYfhGf PcQ eGdg ef GdCOhjICSeGf Ch KdGKI , hcd ePchQ ai HGHg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B13 - (3U(B217s
(3HgG LOGhd HCSeGA HYV GdfHGJGJ hGdCOhjI hNhGUgGs
(3OGNdgG cQGQjS HNW eZGjQ hcJHJ GdYfGhjf HNWg eLhOs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B64 s
Keywords: (3GdWHs